The Winds and Currents Mission Concept - Rodríguez, Ernesto; Bourassa, Mark; Chelton, Dudley; Farrar, J. Thomas; Long, David; Perkovic-Martin, Dragana; Samelson, Roger (Frontiers in Marine Science, 2019)
The Winds and Currents Mission (WaCM) is a proposed approach to meet the need identified by the NRC Decadal Survey for the simultaneous measurements of ocean vector winds and currents. WaCM features a Ka-band pencil-beam Doppler scatterometer able to map ocean winds and currents globally. We review the principles behind the WaCM measurement and the requirements driving the mission. We then present an overview of the WaCM observatory and tie its capabilities to other OceanObs reviews and measurement approaches.